If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -1y = 2x + 14 + y Reorder the terms: 26 + -1y = 14 + 2x + y Solving 26 + -1y = 14 + 2x + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 26 + -1y + -1y = 14 + 2x + y + -1y Combine like terms: -1y + -1y = -2y 26 + -2y = 14 + 2x + y + -1y Combine like terms: y + -1y = 0 26 + -2y = 14 + 2x + 0 26 + -2y = 14 + 2x Add '-26' to each side of the equation. 26 + -26 + -2y = 14 + -26 + 2x Combine like terms: 26 + -26 = 0 0 + -2y = 14 + -26 + 2x -2y = 14 + -26 + 2x Combine like terms: 14 + -26 = -12 -2y = -12 + 2x Divide each side by '-2'. y = 6 + -1x Simplifying y = 6 + -1x
| 3(-4/5+4x)=558/5 | | 6p^2+25p-119= | | (x+2)/(3x+8)=2/5 | | 9x^2-81= | | 30x^2+17x-21=0 | | 6t/5=4 | | 7x+12=3x+96 | | x^2+3x+8= | | d^2-3d=0 | | 2x+3/2=(x)2 | | 2(x+4)-5=37 | | 10-2x=-4+2 | | 84=12(2y-13) | | 8h^2-38h+9= | | 5a^2-9a+5= | | 3y-3ty+49=7y+50-5y | | h^2-15h+26=0 | | r^2+r-650= | | 5m^2-2m=-m+3m^2 | | 3x+4y(38-x)=130 | | 6t-7=8+t | | 3x^2-19x+40= | | 6a+5b=52 | | 0.05(x+60)-0.08(x-10)=2.9 | | 3x+4y=130 | | 4d^2+29d-60= | | 7x=52-3y | | 4x^2+33x+340= | | 3.5*0.5*1.5= | | 0.05-0.02(6-3P)=0.06(P-4)-0.28 | | 36w^2-289= | | 7x+3y=52 |